Hubungan Pendidikan dan Ekonomi dalam Investasi - Nazila Nasywa Maulida; M. Ikhsan; Muhammad Yasin (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Education and the economy have a very close relationship and influence each other. Education is an important factor in determining the quality of human resources and economic growth in a country. The formulation of the problem is how the relationship between education and economic growth and also how education can be seen as an investment. The purpose of this research is to describe the relationship between education and economic growth in SDIT Daarussalaam Sangatta Utara. This research uses and investment in SMPIT Daarussalaam Sangatta Utara. Education and the economy have a close relationship. Education improves the quality of human capital by providing skills and knowledge that make individuals more productive and innovative, and contributes to the economy. Also, education is an important investment that requires money and effort with the expectation of significant long-term returns.